Helyi termékek a vidéki térségek társadalmi-gazdasági fejlődésének szolgálatában - Kalmárné Hollósi, Erika; Vargová, Zuzana (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
Local products play a central role in the concept of multifunctional farming, sustainable development, regional competitiveness and regional identity. The study introduces the results of a research carried out in the West-Transdanubian region in Hungary on regional values and local products. We have found that most of the interviewees were unaware of environmental issues, agricultural production or local food processing in the region. These elements are important factors of regional (economical and social) potential and should be highly utilised in order to maintain and increase competitiveness of a region. The production, marketing and sales of local products increase competitiveness in rural areas, but only if local products are imbedded in the actual practise and applied tools of multifunctional agriculture, integrated rural- and regional development.